Mademoiselle Mom - Parent, Nancy; Disney Storybook Artists (New York, NY Harper, an imprint of HarperCollinsPublishers, 2019)
When her mom gets sick, Nancy decides to help around the house by cleaning up and watching her sister JoJo.
Keywords: Fancy Nancy -- (Fictitious character) -- Juvenile fiction; Fancy Nancy -- (Fictitious character) -- Fiction; Helping behavior in children -- Juvenile fiction; Helpfulness -- Fiction